MARK-AGE population: From the human model to new insights. (November 2015) - Capri, Miriam; Moreno-Villanueva, María; Cevenini, Elisa; Pini, Elisa; Scurti, Maria; Borelli, Vincenzo; Palmas, Maria Giustina; Zoli, Marco; Schön, Christiane; Siepelmeyer, Anne; Bernhardt, Jürgen; Fiegl, Simone; et al.
Highlights: The human model within MARK-AGE project contains innovative concepts. Cells/tissues-age-related biomarkers could mirror ageing process at systemic level. Human biomarkers network is opening a new field to monitor ageing rate.